2020
DOI: 10.1063/1.5142290
|View full text |Cite
|
Sign up to set email alerts
|

Transition from ambipolar to free diffusion in an EUV-induced argon plasma

Abstract: Extreme Ultraviolet (EUV) optical components used in EUV lithography tools are continuously impacted by an exotic and highly transient type of plasma: EUV-induced plasma. Such an EUV-induced plasma is generated in a repetitive fashion upon sending a pulsed beam of high energy (92 eV) photons through a low-pressure background gas. Although its formation occurs on a time scale of ∼100 ns, it is the plasma's decay dynamics on longer time scales that dictates the fluxes and energy distribution of the produced ions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…Freiberg and Weaver [85] showed that the transition starts when Λ/λ De ~100. Platier et al [88] have recently measured that the transition starts at Λ/λ De ~6, which is significantly lower than 100. The difference was explained by the influence of diffusion (evaporative) cooling of the free electrons [36][37][38][39][40][41].…”
Section: Modeling Of Temporal Plasma Afterglow Dust Charges and Dust ...mentioning
confidence: 90%
See 1 more Smart Citation
“…Freiberg and Weaver [85] showed that the transition starts when Λ/λ De ~100. Platier et al [88] have recently measured that the transition starts at Λ/λ De ~6, which is significantly lower than 100. The difference was explained by the influence of diffusion (evaporative) cooling of the free electrons [36][37][38][39][40][41].…”
Section: Modeling Of Temporal Plasma Afterglow Dust Charges and Dust ...mentioning
confidence: 90%
“…It was found again that the mean residual charge is negative, but the tail of the distribution extends into the positive-charge region. Numerical simulations taking into account the discreteness of the charging process [84] and taking into account the transition from ambipolar to free diffusion [42][43][44][85][86][87][88] for the evolution of the plasma parameters were performed [82]. The existence of positively charged particles was then explained by the relative broadening of the dust charge distribution in the late stage of the plasma afterglow.…”
Section: Dust Dynamics Dust Decharging and Residual Charges In Plasma...mentioning
confidence: 99%
“…From this point onward, free diffusion governs the decay as can be seen from the steep decline of the signal before the noise band is reached. 16 The (quasi-)steady state electron density values depicted in Fig. 11 by the (volume-averaged) MCRS data points as a function of the argon pressure facilitate a comparison with the numerical model values for the electron density and the profile-corrected MCRS values obtained in Sec.…”
Section: Articlementioning
confidence: 85%
“…scitation.org/journal/rsi (pristine) radio-frequency discharges, [9][10][11] microwave-induced plasmas, 12,13 dust-forming plasmas, 14,15 extreme ultraviolet photoninduced plasmas, [16][17][18] and ultracold plasmas. 19 Despite the frequent use of these microwave-based techniques, one of the most stringent assumptions potentially undermining the accuracy of the methods is that of a uniform plasma medium, which is fundamental in the interpretation of the experimental data.…”
Section: Articlementioning
confidence: 99%
“…In addition to the two decay regimes of the afterglow of an Extreme Ultraviolet (EUV) photoninduced plasma described in the literature [2], a third decay phase of this type of plasma has only recently been identified [3]. This discovery was enabled by a dramatically improved lower detection limit of the governed diagnostics.…”
Section: First Criterion: Ambipolar Diffusionmentioning
confidence: 99%